Iterations of Loss : Mutilation and Aesthetic Form, al-Shidyaq to Darwish - Sacks, Jeffrey (Book collections on Project MUSE., 2015)
In a series of exquisite close readings of Arabic and Arab Jewish writing, Jeffrey Sacks considers the relation of poetic statement to individual and collective loss, the dispossession of peoples and languages, and singular events of destruction in the nineteenth, twentieth, and twenty-first centuries. Addressing the work of Mahmoud Darwish, Ahmad Faris al-Shidyaq, Elias Khoury, Edmond Amran El Maleh, Shimon Ballas, and Taha Husayn, Sacks demonstrates the reiterated incursion of loss into the time of life-losses that language declines to mourn. Language occurs as the iteration of loss, confoun.